Proceedings of the Second International Conference on Computer and Communication Technologies IC3T 2015, Volume 3 - Satapathy, Suresh Chandra; Raju, K. Srujan; Mandal, Jyotsna Kumar; Bhateja, Vikrant; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2016)
The book is about all aspects of computing, communication, general sciences and educational research covered at the Second International Conference on Computer & Communication Technologies held during 24-26 July 2015 at Hyderabad. It hosted by CMR Technical Campus in association with Division - V (Education & Research) CSI, India. After a rigorous review only quality papers are selected and included in this book. The entire book is divided into three volumes. Three volumes cover a variety of topics which include medical imaging, networks, data mining, intelligent computing, software design, image processing, mobile computing, digital signals and speech processing, video surveillance and processing, web mining, wireless sensor networks, circuit analysis, fuzzy systems, antenna and communication systems, biomedical signal processing and applications, cloud computing, embedded systems applications and cyber security and digital forensic. The readers of these volumes will be highly benefited from the technical contents of the topics.
Chapter 1. Gesture Controlled Wireless Device for Disabled -- Chapter 2. Implementation of Genetic Algorithm for Optimization of Network Rout -- Chapter 3. An Investigation of Gabor PCA and Different Similarity Measure Techniques for Image Classification -- Chapter 4. A Low Power-high Speed Double Manchester Carry Chain with Carry-skip Using D3L -- Chapter 5. Study and Analysis of Electrocardiography Signal in Time Domain for Computation of R-peak Value for Sleep Apnea Patient -- Chapter 6. Design and Implementation of Two Wheeled Self Balancing Vehicle Using Accelerometer and Fuzzy Logic -- Chapter 7. A Time Efficient Secret Image Sharing Scheme for Group Authentication System without Pixel Expansions -- Chapter 8. Imputation of Missing Gene Expressions for DNA Microarray Using Particle Swarm Optimization -- Chapter 9. Deep Belief Network Based Part of Speech Tagger for Telugu Language -- Chapter 10. On Context Awareness for Multi-Sensor Data Fusion in IoT -- Chapter 11. CRiPT : Cryptography in Penetration Testing -- Chapter 12. Simultaneous Localization and Mapping for Visually Impaired People for Outdoor Environment -- Chapter 13. Automatic ECG Image Classification Using HOG and RPC features by Template Matching -- Chapter 14. Enhancement of Fuzzy Rank Aggregation Technique -- Chapter 15. Intelligent Tele-communication System Using Semantic Based Information Retrieval -- Chapter 16. Minimizing Excessive Handovers by Using Optimized Cuckoo Algorithm in Heterogeneous Wireless Networks -- Chapter 17. Audio Songs Classification Based on Music Patterns -- Chapter 18. Software Reliability Based on Software Measures Applying Bayesian Technique -- Chapter 19. On Context Awareness and Analysis of Various Classification Algorithms -- Chapter 20. Neural Network Based Automated Priority Assigner -- Chapter 21. Design of IMC Controller for TI TO Process with Dynamic Close-loop Time Constant -- Chapter 22. All Optical SOA-MZI Based Encryption Decryption System Using Co-propagating Optical Pulses and CW Wave at 40 Gb/s -- Chapter 23. Exploiting Common Nodes in Overlapped Clusters for Path Optimization in Wireless Sensor Networks -- Chapter 24. Maximizing Availability and Minimizing Markesan for Task Scheduling in Grid Computing Using NSGA II -- Chapter 25. Moving Object Detection for Visual Surveillance Using Quasi-Euclidian Distance -- Chapter 26. iOTA: Internet of Things Application -- Chapter 27. Improving Performance of Wireless Mesh Networks Through User Association Method -- Chapter 28. Characterization of Human Fingernails Using Iterative Thresholding Segmentation -- Chapter 29. Confidential Terms Detection Using Language Modeling Technique in Data Leakage Prevention -- Chapter 30. Estimation of Respiration Rate from ECG Using Canonical Components Analysis and Ensemble Empirical Mode Decomposition -- Chapter 31. An Efficient On-chip Implementation of Reconfigurable Continuous Time Sigma Delta ADC for Digital Beam-forming Applications -- Chapter 32. Random Forest for the Real Forests -- Chapter 33. Hybrid GA and PSO Approach for Transmission Expansion Planning -- Chapter 34. Pattern Detection Framework for MRI Images and Labeling Volume of Interest (VoI) -- Chapter 35. A Distributed Spanning Tree Based Dynamic Self Organizational framework for Web Server -- Chapter 36. Recursive Ant Colony Optimization Routing in Wireless Mesh Network -- Chapter 37. Image Processing Representation by Using Binary Image; Grayscale, Color Image and Histogram -- Chapter 38. A Vector Space Model Approach for Web Attack Classification Using Machine Learning Technique -- Chapter 39. Formal Verification of Secure Authentication in Wireless Mesh Network (SAWMN) -- Chapter 40. Visual K-Means approach for HandlingClass Imbalance Learning -- Chapter 41. A Framework for Discovering Important Patterns through Parallel Mining of Protein-protein Interaction Network -- Chapter 42. Implementing DNA Encryption Technique in Web Services to Embed Confidentiality in Cloud -- Chapter 43. An Efficient Motion Detection Method Based on Estimation of Initial Motion Field Using Local Variance -- Chapter 44. A Survey on Texture Image Retrieval -- Chapter 45. Converged OAM -- Chapter 46. Rule Reduction of a Neuro-Fuzzy PI Controller with Real-Time Implementation on a Speed Control Process -- Chapter 47. Construction of Binary and Non-binary LDPC like Codes from Kernel Codes -- Chapter 48. Simulation Level Implementation of Face Recognition under Uncontrolled Environment -- Chapter 49. Analyzing State of the Art Techniques for Fusion of Multimodal Biometrics -- Chapter 50. Genetic Algorithmic Approach to Mitigate Starvation in Wireless Mesh Networks -- Chapter 51. Handwritten Indic Script Identification from Document Images - A Statistical Comparison of Different Attribute Selection Techniques in Multi-classifier Environment -- Chapter 52. An FPGA Based Embedded System for Real time Data Processing -- Chapter 53. Clustering of Noisy Regions (CNR) - A GIS Anchored Technique for Clustering on Raster Map -- Chapter 54. Performance of Brightness Enhancement Technique for Narrow-band and White-band Images -- Chapter 55. Z Transformation Based High Payload Authentication Technique with Higher Region of Convergence Value (ZATHRoc) -- Chapter 56. Breast Tissue Density Classification Using Wavelet Based Texture Descriptors -- Chapter 57. On New Families Related to Bernoulli and Euler Polynomials -- Chapter 58. Vehicular Ad-hoc Networks: Trimming Pile-Ups in Data Dissemination using HTPVANET Algorithm -- Chapter 59. Information Extraction from Research Papers Based on StatisticalMethods -- Chapter 60. Artificial Neural Network Classifier for Intrusion Detection System in Computer Network -- Chapter 61. Edge Detection on an Image Using Ant Colony Optimization -- Chapter 62. Cryptography Technique for a Novel Text Using Mathematical Functions -- Chapter 63. A New Hybrid Approach for Document Clustering Using Tabu Search And Particle Swarm Optimization TSPSO -- Chapter 64. An Effective and Efficient Clustering Based on k-Means Using MapReduce and TLBO -- Chapter 65. Detection of Sinkhole Attack in Wireless Sensor Network -- Chapter 66. Enhancement of Stream Ciphers Security Using DNA -- Chapter 67. Object Recognition with Discriminately Trained Part Based Model on HOG (Histogram of Oriented Gradients) -- Chapter 68. Accuracy Assessment of the Images Classification Using RBF with Multi Swarm Optimization Methodology -- Chapter 69. Microstrip Patch Antenna Array with Metamaterial Ground Plane for Wi-MAX Applications -- Chapter 70. Tracking and Speed Estimation of Moving Vehicle for Traffic Surveillance System -- Chapter 71. Authentication of Audio Signals in Frequency Domain (AASF).
Keywords: Telecommunication; Computational intelligence; Signal processing; Computer networks .; Communications Engineering, Networks; Computational Intelligence; Signal, Speech and Image Processing; Computer Communication Networks